Pengaruh Struktur Modal, Likuiditas Dan Resiko Kredit Terhadap Nilai Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2021 - Wanda Hamidah; Hidayah Wiweko; Ahmad Faisol (STIE AMKOP, 2023)
The purpose of this study is to obtain empirical evidence of the effect of capital structure, liquidity and credit risk on firm value. The object of this research is the banking sub-sector companies listed on the Indonesia Stock Exchange during 2010-2021. Samples were selected using purposive sampling. Companies that meet the sample criteria are 16 companies. The data used in this study is secondary data taken from the official website of the Indonesia Stock Exchange. The analysis technique used is descriptive statistics, classical assumption test, multiple linear regression and hypothesis testing. The results of the study show that capital structure has no effect on firm value, liquidity has a significant negative effect on firm value and credit risk has a significant negative effect on firm value. Keywords: Capital structure, Liquidity, Credit risk and Firm Value